Улонлэн муэз: кылбуръёс но поэмаос / Александр Белоногов - Белоногов Александр Егорович (Удмуртия, 1982)
Экземпляры: 1 (20140430) / Инвентарный номер: 4734 / Сис.шифр: С(Удм) / Авт.знак: Б 43 / ГРНТИ: 17.82.10 / ББК: 84(Удм)